Teknik Komunikasi Majelis Permusyawaratan Ulama (MPU) Aceh dalam Mensosialisasikan Keharaman Game Higgs Domino Island di Kampung Tanjung Keramat - Chairozi, Fachri (AHKAM, 2023)
In general, this study aims to determine the communication techniques used by the Ulama Consultative Assembly in socializing the prohibition of the Higgs domino island game in Kampung Tanjung Keramat. This study also aims to determine the media and the obstacles faced by the Ulama Consultative Assembly during the socialization process. This research uses a qualitative approach with descriptive methods, this research is a field study. The collection of data obtained during the research is using semi-structured interviews and documentation studies. The results of the study showed that the Ulama Consultative Assembly used several communication techniques in conveying the socialization of the higgs domino island game's prohibition. The Ulama Consultative Assembly also uses the same method as before because the methods usually used are effective in the delivery process, such as the use of informative techniques, persuasion techniques in the form of rewards, as well as techniques to frighten audiences and human relations techniques to attract the hearts of audiences and make it easier for them to To convey its socialization, the Ulema Consultative Council also uses media in the form of posters and meetings to make it easier for them to socialize the higgs domino island game's prohibition. In socializing the Ulama Deliberative Council also faced obstacles in the form of funding, synergy and psychology that were not profitable when conducting socialization in their delivery, but they continued to work so that the obstacles that occurred could be resolved properly and the socialization conveyed could be accepted and implemented by the community.